La terre du pouvoir, le pouvoir de la terre - Nick Miszak; Alessandro Monsutti (Revue des Mondes Musulmans et de la Méditerranée)
This article aims to demonstrate that the language of legal claims and the use of violence do not consistently stand in opposition to each other. They constitute modes of gaining and maintaining access to resources that subtly overlap in practice and are mutually constitutive elements. Through the analysis of a conflict over land at the rural–urban fringe of Kabul, the capital of Afghanistan, we examine how these two modes link struggles over land control to broader political geographies of power. Following important changes in the material conditions that have led to the expansion of the city and the transformation of the rural–urban fringe, territorialized power appears as a pre-condition for control of the circulation of people, goods, money, information and ideas, allowing us to add landscapes, the circulation of land, to the five categories famously distinguished by Appadurai (1999) as a means of organizing the study of the world’s culture and economy.